#### Answer

$$y=x \left( x -\ln x +C\right).$$

#### Work Step by Step

Rewrite the equation as
$$y'-x^{-1}y=x-1$$
This is a linear equation and has the integrating factor as follows
$$\alpha(x)= e^{\int P(x)dx}=e^{\int- x^{-1} dx}=e^{-\ln x}=\frac{1}{x}$$
Now the general solution is \begin{align} y&=\alpha^{-1}(x)\left( \int \alpha(x)Q(x)dx +C\right)\\ &=x \left( \int 1 -\frac{1}{x} dx +C\right)\\ &=x \left( x -\ln x +C\right) \end{align}
Thus, the general solution is
$$y=x \left( x -\ln x +C\right).$$